Carbon-vacancy modified graphitic carbon nitride: enhanced CO2 photocatalytic reduction performance and mechanism probing. Issue 4 (9th January 2019) - Shen, Meng; Zhang, Lingxia; Wang, Min; Tian, Jianjian; Jin, Xixiong; Guo, Limin; Wang, Lianzhou; Shi, Jianlin
Abstract : Enhanced charge carrier generation, attenuated exciton-effect as well as upgraded CO2 adsorption/activation lead to a promoted CO2 -to-CO photocatalytic conversion ability for C-vacancy modified GCN. Abstract : The obstacles to achieving high CO2 photoreduction performance on graphitic carbon nitride (GCN) are commonly ascribed to its weak CO2 activation capability and low charge carrier concentration. To overcome these obstacles, here we report a new class of GCN with C vacancies intentionally introduced by heat treatment in an NH3 atmosphere. GCN with enriched C vacancies exhibits more than two times higher CO2 -to-CO conversion rate than pristine GCN. Our detailed characterization reveals that the improved CO2 reduction performance of this carbon-vacancy modified GCN is attributed to the enhanced CO2 adsorption/activation, upshifted conduction band and elevated charge carrier concentration and lifetime. Moreover, we discover that the introduction of C vacancies into GCN could attenuate the exciton-effect and favor the charge carrier generation. These results not only provide insights on regulating the structure of GCN to promote its CO2 photoreduction performance, but also pave the way to tune the exciton effect and charge carrier concentration in GCN to facilitate photoinduced electron–hole separation and charge-carrier-involved photocatalytic reaction.